Some Components of Philosophical nature Constitutives of Prof. Mario Tourasse Teixeira's Thought Alguns Elementos de Natureza Filosófica Constitutivos do Pensamento do Prof. Mario Tourasse Teixeira - Romélia Mara Alves Souto (Universidade Estadual Paulista, 2008)
In this paper I endeavor to show the interest shown by Prof. Mario Tourasse Teixeira with respect to the production of mathematical knowledge and the ideas underlying the concepts of creativity in mathematics which he used and which permeate the work he supervised. My aim was to organize ideas dispersed throughout the work produced by his pupils, recorded in manuscripts or elaborated as texts and published by Prof. Tourasse in SAPO newsletters. In an attempt to capture his thoughts on Mathematics and Education, I tried to establish connections between documents which, explicitly or not, bear his mark. I believe that the merit of this effort lies in organizing, systematizing and presenting, for the first time, a draft of Prof. Mario Tourasse Teixeira's mathematical-philosophical thought. Keywords: Mario Tourasse Teixeira. Mathematics History. Mathematics Education. History of Mathematics Education. Neste trabalho procuro mostrar o interesse que o Prof. Mario Tourasse Teixeira manifestava em relação ao dinamismo do conhecimento matemático e as idéias subjacentes ao conceito de criatividade em matemática por ele utilizado e que permeiam todos os trabalhos que orientou. Meu intuito foi organizar idéias dispersas em vários trabalhos realizados por seus alunos, registradas em alguns manuscritos ou elaboradas em textos publicados pelo Prof. Mario Tourasse, anonimamente, nos boletins do SAPO. Na tentativa de captar seu pensamento sobre Matemática e Educação, busquei estabelecer conexões entre os diversos documentos que, explicitamente ou não, guardam seu registro. Acredito que o mérito desse esforço reside em organizar, sistematizar e apresentar pela primeira vez, um esboço do pensamento matemático-filosófico do Prof. Mario Tourasse Teixeira. Palavras-chave: Mario Tourasse Teixeira. História da Matemática. Educação Matemática. História da Educação Matemática.